Cross-flow determination by transcranial Doppler predicts clamping ischemia in patients undergoing carotid endarterectomy - Attigah, Nicolas; Demirel, Serdar; Ringleb, Peter A.; Hinz, Ulf; Hyhlik-Dürr, Alexander; Böckler, Dittmar (The journal of cardiovascular surgery, 2015)
AIM: Aim of the paper was to assess the reliability of preoperative cross-flow determination by transcranial Doppler measurement (TCD) to detect clamping ischemia in patients undergoing carotid endarterectomy with selective shunting. - METHODS: Retrospective one-to-one matched-pair analysis of 72 patients undergoing carotid endarterectomy with preoperative TCD scanning. Matching criteria were gender, degree of contralateral stenosis and the type of stenosis (asymptomatic or symptomatic). - RESULTS: Patients in need for a secondary shunt insertion had significantly less cross-flow in preoperative TCD measurement (N.=14; 38.89%) compared to the control group (N.=32; 88.89%: P=0.0001%). The sensitivity of the cross-flow determination to predict clamping ischemia was 88.9%, the specificity 61.1%. The risk of developing a clamping ischemia in the absence of a cross-flow was 12 fold higher (OR: 12.6; 95% CI: 3.7-43.3). The existence of circulatory impairment of the MCA was associated with the presence of a collateral flow in the ACoA (OR 3.21; P=0.0531; likelihood ratio test 0.0481). Other factors like renal insufficiency, the degree of stenosis or the stump pressure showed no association with a cross-flow of the ACoA in a multivariate model. - CONCLUSION: TCD scanning is highly reliable to detect cross-flow prior to carotid surgery and thus helpful to identify patients at risk for clamping ischemia and need for shunting.